Confirmation of Nosocomial Transmission of Hepatitis C Virus by Phylogenetic Analysis of the NS5-B Region - Norder, Heléne (American Society for Microbiology, 1998)
Four hepatitis C virus transmission chains at three dialysis units were disclosed by limited sequencing; three of these were disclosed by analysis of the NS5-B region of the genome. Dialysis on the same shift as that during which infected patients were dialyzed was the common factor for seven patients in two chains. Two nurses exposed to needle sticks and their sources of infection constituted two other chains. The strains of three chains belonged to subtype 1a and formed clusters with an intrachain variability of 0 to 6 nucleotides compared to 8 to 37 nucleotides for unrelated strains within this subtype. The clusters were supported by bootstrap values ranging from 89 to 100%.